Effect of nutrient supplementation on growth performance and carcass characteristics of Nellore ram lambs – An on-farm evaluation study - GIRISH, P S; REDDY, BASWA P; RAMAKRISHNA, C; REDDY, Y RAMANA; CHAVA, SATISH; KONDAIAH, N (The Indian Journal of Animal Sciences, 2012)
A field study was conducted in the Nellore sheep breeding tract on growth parameters of 447 Nellore (jodipi) ram lambs, out of which 30 lambs were fed on traditional grazing (control) and 417 lambs on natural grazing along with nutrient supplementation (treated) i.e. feeding of balanced concentrate feed. Average initial body weight of the lambs under control group and treated group were 13.60 ± 0.58 kg and 13.38 ± 0.07 kg, respectively. After 90 days of rearing, lambs under treated group showed better growth rates with significantly (P < 0.01) heavier final average body weight (23.11±0.19 g) as compared to those of control group (22.05±0.11 kg). Growth studies revealed that ram lambs fed on natural grazing along with nutrient supplementation (treated) showed significantly higher average daily gain. Carcass studies also revealed that dressing percentage, cut up parts yield and by- products yield were also better in lambs under treated group compared to those of control group due to better nutritional status in supplemented lambs. This study was part of field demonstration trials to farmers on benefits of growing ram lambs to optimum weight and nutritional intervention for getting higher growth rate.